Escenarios de competencia en las cadenas globales de producción en la industria automotriz: un estudio de caso del Grupo Stellantis y su planta ensambladora en Vigo - Rísquez Ramos, Mario (Papeles de Europa, 2023)
The transformations that have taken place in recent decades in the way in which production and trade are organised in the global economy invite us to revisit and revise the discussion on the conceptual coordinates on which the debate on competition and competitiveness is approached. This paper presents a theoretical-interpretative proposal to characterize competition in the context of global production chains. To this end, a case study of the automotive industry is carried out, from which we will also deepen the analysis of how the process of modularization of production impacts on the competition between assembly plants of the same business group.